1991 census of population and housing. Census characteristics of Queensland. - Australian Bureau of Statistics (Canberra : Australian Bureau of Statistics, 1993)
Counts of people and dwellings cross-classified by social and demographic characteristics for Queensland, and for the Statistical Division of Brisbane. Tables are grouped into broad categories, such as age, birthplace, and labour force. However, all characteristics are listed separately in the index, along with the corresponding numbers of tables in which they appear.
Catalogue no. 2710.3.
Includes tables.
Includes index.
Keywords: Queensland -- Census, 1991.; Queensland -- Population -- Statistics